Sharing the burden of financing the green climate fund in the Post-Kyoto era - Cui, Lianbiao; Gui, Huangbao (International journal of climate change strategies and management, 2015)
Purpose – The purpose of this paper is to design several methods for enforcing developed countries’ responsibilities under the Green Climate Fund (GCF). The GCF has been one of the core subjects of the world climate summits held under the United Nations Framework Convention on Climate Change. However, the development of the GCF has not progressed smoothly, and many concerns remain unresolved. Design/methodology/approach – This paper illustrates three approaches for financing the GCF that vary in terms of the relative weights accorded to environmental responsibility and economic capacity. These three methods include the historical responsibility (HR) principle, the ability to pay (AP) principle and the preference score compromises (PSC) approach (which is a combination of the HR and the AP principles). Findings – The empirical analysis demonstrates that the USA is the largest contributor to the GCF under the HR principle due to the volume of its historical emissions, whereas the European Union bears the greatest financial responsibility under the AP principle, based on its gross domestic product. Under the PSC approach, the European Union and the USA each undertakes a financial burden that approximates 40 per cent of the total financing for the GCF. These nations are followed by Japan, which has a share of almost 9 per cent. Originality/value – This study is the first attempt to introduce the PSC concept into discussions regarding GCF financing. A scheme of burden sharing that combines environmental responsibility and economic capacity factors is developed and introduced. The respective weights assigned to the two factors are determined based on the Borda rule in voting theory, which avoids the arbitrary allocation of weights between the HR and the AP. These findings will be useful for mobilising the GCF in the Post-Kyoto era.